Performance Appraisal System in Indian Organisations: A Study (International Journal of Innovative Research in Engineering & Management, 2021)
This paper examines the variables that influence India's  performance evaluation system. The services industry  encompasses a broad range of operations, including  telecommunication, satellite mapping, and software applications.  The process of detecting, evaluating, and enhancing human  performance in companies is known as performance assessment  or evaluation. In order to enhance future performance, a good  evaluation mechanism should not only correctly assess present  performance levels, but also provide methods for rewarding  strengths, detecting shortcomings, and sending such data back to  rates. We provide an overview of several common performance  evaluation methods in India in this article. Because managers are  always under pressure to enhance the performance of their  organizations, performance management has grown increasingly  important in recent years. It is now well acknowledged that an  organization's performance has an impact on its ongoing  existence and success.
Keywords: Appraisal Approaches; Appraisal Types; Performance appraisal; Performance evaluation; Progress Evaluations